Inclusive Education Policies in Sub-Saharan Africa a Pathway to Educational Access for All - Agbor Ekama Prisca Anne (International Journal on Integrated Education, 2022)
Many countries in Sub-Saharan Africa are struggling to meet the educational needs of those children and youth who are relatively easy to reach. This raises concerns about how the region will ensure that the most disadvantaged can complete primary education. Inclusive Education is designed to ensure that every child has access to quality education, irrespective of gender, language, ability, religion, nationality or other characteristics. This is to support meaningful participation and learning alongside their peers in other to develop their full potential. (Save the Children 2016:6). The stipulation that students ‘learn alongside’ their peers, ‘within their community’ alludes to the historical practice of providing segregated, ‘special’ education for Children with Disabilities. The paper confirms that failures to prioritize primary enrolment leave millions of teenagers out of school later on. The out-of-school rate in sub-Saharan Africa is 21% for children of primary school age (about 6-11 years), 34% for youth of lower secondary school age (12-14 years) and 58% for youth of upper secondary school age (15-17 years), according to UIS data. Provisions within the national educational systems have demonstrated the difficulties educators face to guarantee inclusive education in Sub-Saharan Africa. Some of these challenges include, but not limited to, creating activities that includes all learners, inadequate teachers’ aid for learners with special needs, lacking experience in an inclusive setting, lacking experience with severe and profound disabilities etc.